Validação de protocolo para a assistência de enfermagem ao paciente no transoperatório de cirurgia cardiovascular com circulação extracorpórea - Albuquerque, Carla Lorenna Ferreira de (2019)
Objective: to construct and validate a protocol for the nursing care of the patient in the transoperative period of cardiopulmonary bypass with cardiopulmonary bypass (CPB). Method: methodological, quantitative study, developed in two stages referring to the construction and validation of the content of the protocol. The validation was performed using the Delphi technique in two rounds, with the participation of 14 experts as evaluators of each variable proposed in the protocol. The selection of experts was by snowball sampling. The items included in the instrument were evaluated using the Likert scale, with categories in four levels of importance and the selection of a single response for each analyzed variable, and by the analysis of the content of the instrument with the universal agreement of the index of content validity ( UA-IVC) and the Content Validity Index (CVI). Results: items related to surgical and patient room preparation, intraoperative care and report (intraoperative information) for the ICU were validated. The items obtained a mean score of 90% and UA-IVC concordance of 89%, in which eight items reached the 100% IVC and one the 93% IVC item; however, one item did not reach the IVC ≥80% being recommended the merger together with another item. Conclusion: the results of this study reflect the importance of the nurse's role in the implementation of a protocol with the purpose of guiding safe surgery practices that promote patient safety and effective communication within the context of cardiovascular surgeries.